Soil organic carbon and infiltrability in relation to distance from trees (Vitellaria paradoxa) with and without termite mounds in a parkland of central Burkina Faso - Hedemyr Joelsson, Klara (SLU/Dept. of Forest Ecology and Management, 2012)
In semi-arid Burkina Faso access to water is crucial for crop-growth. Most common cropping system in the region is parklands, where crops are grown in association with trees. This study investigates if trees and termites influence steady-state infiltrability, soil carbon content, bulk density and macro-porosity in a specific parkland in Saponé, Burkina Faso. Infiltrability was measured with a double-ring infiltrometer and steady-state infiltrability was estimated by Philip’s equation. Bulk density, macro porosity and carbon content were sampled and analysed. Measurements were conducted in 11 transects; five transects in small openings (20–31 m between trees) and six in large openings (68–127 m between trees). Each transect went from one tree with a termite mound to a tree without termites. The results showed significantly higher steady-state infiltrability close to trees, with and without termites compared to the centre of the openings. Infiltrability decreased with increased distance from trees. No such decrease occurred when small openings was analysed separately. Bulk density increased with increased distance from trees. Bulk density had a reversed linear relation with steady-state infiltrability. Carbon content in top soil was higher under trees than in openings. At 30-35 cm depth macro porosity decreased with increased distance to trees, with and without termites. Measurements from trees with termites had high variance for all variables. Trees improve soil structure by lowering bulk density, increase the amount of macro-pores, raise the carbon content and thus improve infiltrability. Maintaining parkland can be a good way of maintaining trees in a landscape and tree density is shown to matter for soil quality and may have large importance for groundwater recharge.